Harnessing and advancing knowledge in social enterprises: Theoretical and operational challenges in the refugee settlement experience. Issue 2 (4th May 2019) - Kong, Eric
ABSRACT: A better understanding of the role of social enterprises in the refugee settlement experience likely assists in transferring refugees' prior labour market experience into the receiving-country's labour market and facilitating further knowledge creation for life satisfaction and self-reliance for refugees. A qualitative narrative inquiry approach was adopted to identify the knowledge and learning activities addressing social issues in social enterprises.The paper serves as a milestone in examining the role of social enterprises in harnessing and advancing knowledge in refugee settlement experience.